509PSecond-line treatment after first-line vinorelbine in advanced platinum unfit NSCLC patients: An exploratory analysis of randomized Tempo-Lung trial. (24th November 2019) - Camerini, A; Morabito, A; Montanino, A; Bernabe Caro, R; Grossi, F; Ramlau, R; Ciuleanu, T-E; Ceresoli, G L; Pasello, G; de Marinis, F; Bosch-Barrera, J; Landreau, P; et al.
Abstract: Background: Tempo-Lung trial randomly assessed the role of metronomic oral vinorelbine (OV) vs standard weekly oral vinorelbine in advanced NSCLC patients (pts) unfit to platinum doublets. Little data are available on treatment options after first-line in platinum-unfit pts. Methods: Advanced NSCLC pts unfit to receive platinum doublets (Creatinine clearance <60 ml/min; heart failure NYHA class II-III; hearing loss >G2; any medical condition impairing platinum treatment according to physician's opinion) were randomized to arm A (metronomic): OV 50mg x3/week (wk) or arm B (standard): OV 60 mg/m²/wk cycle 1, then 80 mg/m²/wk. Primary endpoint was progression free-survival without grade 4 toxicity (PFSG4) and secondary efficacy and safety end-point, quality of life (QoL). Data on treatment after failure of first-line vinorelbine were collected. Results: Intention-to-treat population included 165 (arm A 83 - arm B 82) pts. Baseline characteristics were well balanced between both arms. Mean dose intensity by cycle: 73.56 mg/m²/week (arm A), 55.85 mgm²/week (arm B). Median PFSG4 significantly differ in favor of metronomic arm [95%CI]: 4.0 [2.6-4.3] vs 2.2 [1.5-2.9] months (p = 0.0068), HR [95%CI] = 0.63 [0.45-0.88]. Overall treatment related adverse events (61.4% vs 84%): haematological toxicities (27.7% vs 55.6%), G3/4 neutropenia (11% vs 42%), febrile neutropenia (3.6% vs 6.2%) and G3/4 asthenia (4.8% vs 8.6%) were reduced with metronomic OV. It was observed that 40% of patients (subset) had second line treatment: immunotherapy, chemotherapy, protein kinase inhibitor, radiotherapy. No difference was found for changes in EORTC QoL scores. Secondary endpoints will be presented. Conclusions: Metronomic OV could be a suitable option for advanced NSCLC pts unfit to receive platinum doublets. Less toxicity was observed in metronomic arm. QoL scores were similar in both arms. A subset of platinum unfit patients could receive second-line treatment mainly consisting on immunotherapy, chemotherapy. Clinical trial identification: 2014-003859-61. Legal entity responsible for the study: IRPF, Pierre Fabre Medicament. Funding: Pierre Fabre Medicament. Disclosure: A. Camerini: Speaker Bureau / Expert testimony, expert testimony: Pierre Fabre; Travel / Accommodation / Expenses: Roche; Travel / Accommodation / Expenses: Pierre Fabre. A. Morabito: Speaker Bureau / Expert testimony, speaker bureau: Pfizer; Speaker Bureau / Expert testimony, speaker bureau: BMS; Speaker Bureau / Expert testimony, speaker bureau: MSD; Speaker Bureau / Expert testimony, speaker bureau: Roche; Speaker Bureau / Expert testimony, speaker bureau: AstraZeneca; Speaker Bureau / Expert testimony, speaker bureau: Boehringer Ingelheim. F. Grossi: Advisory / Consultancy: Eli Lilly; Advisory / Consultancy: Roche; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Pierre Fabre; Advisory / Consultancy: Boehringer Ingelheim; Advisory / Consultancy: BMS; Advisory / Consultancy: MSD; Advisory / Consultancy: Novartis; Honoraria (self): Eli Lilly; Honoraria (self): Roche; Honoraria (self): AstraZeneca; Honoraria (self): Boehringer Ingelheim; Honoraria (self): Pierre Fabre; Honoraria (self): BMS; Honoraria (self): Novartis; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): BMS; Research grant / Funding (self): MSD. R. Ramlau: Advisory / Consultancy: Roche; Advisory / Consultancy: MSD; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Novartis; Advisory / Consultancy: Boehringer Ingelheim. T-E. Ciuleanu: Advisory / Consultancy: Astellas; Advisory / Consultancy: Janssen; Advisory / Consultancy: BMS; Advisory / Consultancy: Merck Serono; Advisory / Consultancy: Amgen; Advisory / Consultancy: Roche; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Boehringer Ingelheim; Advisory / Consultancy: Lilly; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: MSD; Advisory / Consultancy: Sanofi; Advisory / Consultancy: Servier; Advisory / Consultancy: A et D Pharma; Travel / Accommodation / Expenses: Pfizer; Travel / Accommodation / Expenses: Sanofi; Travel / Accommodation / Expenses: Boehringer Ingelheim; Travel / Accommodation / Expenses: Merck; Travel / Accommodation / Expenses: Servier; Travel / Accommodation / Expenses: Ipsen. G.L. Ceresoli: Advisory / Consultancy: Pfizer; Advisory / Consultancy: Astellas; Advisory / Consultancy: Boehringer Ingelheim. J. Bosch-Barrera: Honoraria (self): Pierre Fabre; Honoraria (self): MSD; Honoraria (self): Roche; Honoraria (self): BMS; Advisory / Consultancy: Boehringer Ingelheim. P. Landreau: Full / Part-time employment: Pierre Fabre. S. Gautier: Full / Part-time employment: Pierre Fabre. C. Ta Thanh Minh: Full / Part-time employment: Pierre Fabre. All other authors have declared no conflicts of interest.